244 Polymorphism of microrna region in the TNFA gene in childhood-onset systemic lupus erythematosus. (April 2019) - Vivaldo, Jessica; Postal, Mariana; Sinicato, Nailu; Marini, Roberto; Niewold, Timothy; Appenzeller, Simone
Abstract : Background: Studies have implicated microRNAs (miRNAs) in the pathogenesis of systemic lupus erythematosus (SLE). miRNAs regulate approximately 90% of the protein-encoding genes and play a central role in various biological processes, including impairment of cell differentiation and proliferation e apoptosis. Polymorphism in miRNA regions of TNFA gene may account for the variations observed in the clinical. The aim of this study was to investigate the presence of polymorphisms of miRNA regions of TNFA gene associated to clinical and laboratory profile of these SLE patients. Methods: Consecutive childhood-onset SLE (cSLE) patients followed at Pediatric Rheumatology Unit of the Unicamp were enrolled in study. Healthy volunteers with were included as control group. A complete clinical, laboratory and neurological was performed in all subjects. cSLE patients were further assessed for clinical and laboratory SLE manifestations, disease activity [SLE Disease Activity Index (SLEDAI)], damage [Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI)] and current therapy. Total dose of corticosteroids and other immunosuppressant medications used since the onset of disease were calculated by data obtained by careful review of the medical charts. We investigated miRNA region of the TNFA gene in cSLE compared to healthy volunteers using DNA Sequencing by Capillary Electrophoresis. Data were compared by non-parametric tests. Results: We included 110 cSLE patients [83 women (75.4%)]. The mean disease duration was 13.18±4.32 (1–20 years). We included as a control group 60 healthy individuals [52 women (86.7%)] recruited from the local community. The mean score of cumulative SLEDAI was 2.88±2.20 (0.09–12.52). The mean of total corticosteroid dose was 23437.54±16656.55 mg. We identified polymorphism rs3093665 (c.*77 A>C) in 8 (7.3%) cSLE patients, polymorphism rs3093666 (c.*419 C>T) in 3 (2.7%) patients and polymorphism rs3093667 (c.*453 G>T) in 2 (1.8%) cSLE patients. Polymorphism rs3093665 is located in a region of interest, into a miRNA region-binding site of miR-452 and polymorphism rs3093667 into a miRNA region-binding site of miR-19a. In the control group, we identified polymorphism rs3093665 in only 1 control. We observed an association between polymorphism rs3093665 and organic brain syndrome (p=0.001), an association between polymorphism rs3093666 and thrombocytopenia (p=0.02) and an association between polymorphism rs3093667 and hematuria (p=0.024). Conclusions: To our knowledge, this is the first study to evaluate polymorphisms in miRNA regions of TNFA gene in SLE. We identified polymorphism rs3093665 and rs 3093667, both into miRNA region-binding sites. Alterations contribute to the development of pathological conditions and clinical disorders in SLE. Funding Source(s): CAPES CNPq FAPESP